'˜DOCTOR PATIENT LANGUAGE BARRIER - COMPROMISING ON QUALITY CARE' - Shoaib, Maria; Ahmed, Syed Ahsanuddin; Mahmood, Syed Uzair; Hafiz, Muhammad Yusuf (Journal of Ayub Medical College Abbottabad, 2016)
Dear Editor, Pakistan is a land of diverse culture and languages, although the official language is English along with national language as Urdu, yet large populations, specially residing in rural areas knows neither of the two languages and have their own native lingo. Hence we have a good number of patients presenting to our outpatient departments who can't explain their symptoms well enough to the doctors encountering language barrier.1 Almost all big teaching hospitals and regional tertiary care units are frequented by patients from far and wide diverse backgrounds. History taking in their local language is a main problem of the students and physicians. Often times a single word uttered by the patient is failed to be comprehend.2 Language barriers have a big impact on doctor patients' relationship if unresolved, it decreases patients' satisfaction. Creates misunderstandings regarding diagnosis, treatment and self-care options.3 It decreases chance of access to primary and preventive care measures. Leaves no counseling impacts on the patient. Thus In order to reach the best health outcome, doctors must communicate effectively across cultures. Looking at this from a general perspective, one can go through all the books on clinical methods and yet get stun when our patient tries to explain his problem in his native language. Thus begins the search for a translator who can understand the patient and share his concerns with the doctor. Also Feels there is a dire need that local terminologies for common symptoms in our local languages should be more often shared with the medical students particularly during the lectures , and great if displayed on charts in the OPD's, for quick reference.4 Efforts to facilitate the physicians' linguistic competence and understanding of diverse health modalities with cultural aspect would surely be helpful for patients comfort, trust and health. We recommend that medical personnel's from diverse backgrounds should register as volunteer translators, and every tertiary care setup should have their own group of language facilitators easily accessible in the hospital to obtain first hand health information from the patients without any barrier. This would be a great effort for comprehensive medical learning, training and would enhance patients' quality of care.